N6-Methyladenosine-Sculpted Regulatory Landscape of Noncoding RNA - Zhang, Zhongyuan; Wei, Wei; Wang, Hao; Dong, Jiangning (Frontiers in Oncology, 2021)
Exploration of the dynamic N6-methyladenosine (m6A) RNA modification in mammalian cells has whipped up a gale in recent years due to its pivotal roles in multiple biological and pathological processes, including cellular reprogramming, fertility, senescence and tumorigenesis. In comparison with the plentiful researches unravelling the effect of m6A modification on eukaryotic messenger RNAs and the emerging role of noncoding RNAs in epigenetic regulation, the reports of the association between noncoding RNAs and m6A modification have been relatively limited. Noncoding RNAs that underwent m6A modification are capable of regulating cell reproduction and metabolism, autophagy, and homeostasis. Moreover, homeostasis of m6A modification can be affected by noncoding RNAs in a broad spectrum of biological activities. Importantly, the co-adjustment and interaction between them is responsible for the cell development, as well as the initiation and progression of diseases. Hence, in this review, we will give an account of recent strides in revealing biological interaction between noncoding RNAs and m6A decoration, and discusses the potential clinical application of interfering with m6A modification.